2002
DOI: 10.1210/me.2002-0055
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Deficiency Syndromes in Mice with Targeted Disruption of Cyp11a1

Abstract: Steroid deficiencies are diseases affecting salt levels, sugar levels, and sexual differentiation. To study steroid deficiency in more detail, we used a gene-targeting technique to insert a neo gene into the first exon to disrupt Cyp11a1, the first gene in steroid biosynthetic pathways. Cyp11a1 null mice do not synthesize steroids. They die shortly after birth, but can be rescued by steroid injection. Due to the lack of feedback inhibition by glucocorticoid, their circulating ACTH levels are exceedingly high; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(69 citation statements)
references
References 21 publications
4
65
0
Order By: Relevance
“…In rodents, both maternal ovarian and fetal placental steroidogenesis were thought to be necessary throughout pregnancy (reviewed in reference 8). However, mouse fetal steroidogenesis appears not to be necessary, as P450scc Ϫ/Ϫ -knockout mice survive to term like the rabbit and die shortly thereafter from adrenal insufficiency (24). We also found that P450scc is expressed in the embryo at E7, in the same region as P450c17 (data not shown).…”
Section: Discussionmentioning
confidence: 59%
“…In rodents, both maternal ovarian and fetal placental steroidogenesis were thought to be necessary throughout pregnancy (reviewed in reference 8). However, mouse fetal steroidogenesis appears not to be necessary, as P450scc Ϫ/Ϫ -knockout mice survive to term like the rabbit and die shortly thereafter from adrenal insufficiency (24). We also found that P450scc is expressed in the embryo at E7, in the same region as P450c17 (data not shown).…”
Section: Discussionmentioning
confidence: 59%
“…This was achieved in P450scc knockout mice (Hu et al, 2002). Remarkably, the homozygous knockout mice were born without embryonic lethality suggesting that P450scc is not essential for survival of mouse embryos.…”
Section: Functions Of Pregnenolone/pregnenolone Sulfate In Vivomentioning
confidence: 99%
“…The other hormones produced by the fetal testis (androgen and INSL3) come predominantly from the fetal Leydig cells. In cases where fetal Leydig cells fail to develop, or androgen production is disrupted, pseudohermaphroditism will occur (Geissler et al 1994, Kremer et al 1995, Caron et al 1997, Clark et al 2000, Hu et al 2002. Transcripts encoding the critical enzymes required for androgen production can be detected in the testis shortly after Leydig cell differentiation (13.0 dpc in the mouse and 35 dpc in the sheep; Greco & Payne 1994, Quirke et al 2001, and testosterone can be detected at around 13.0 dpc in the mouse (Gondos 1980), 35 dpc in the sheep (Quirke et al 2001), and at 7 GW in the human, peaking in the human in the early second trimester (Tapanainen et al 1981, Fowler et al 2009, Scott et al 2009).…”
Section: Fetal Testicular Hormone Productionmentioning
confidence: 99%